Electrical power generation through concentrated solar technology for the southern cities of Iraq - Riyadh Toman Thahab; Ahmed Toman Thahab (International Journal of Electrical and Computer Engineering (IJECE), 2020)
With a continuing mismatch between generating capacity and demand requirements, Iraqi cities are still enduring scheduled power outages. In this work, concentrated solar power (CSP) technology is proposed and designed for Iraqi cities to inject power into distribution networks with the objective of boosting the generating power capacity. Since CSP systems require a preliminary study of the direct normal irradiance (DNI), analyses of monthly data is carried out for each of the candidate cities. This is followed by determination of the amount of solar irradiance that falls on a titled collector per month considering the effects of reflection and diffusion. Finally, a thermal power plant is proposed and simulated using the system advisory model (SAM) per city. Results presented show an encouraging number of metrics and confirm the feasibility of such a plant in southern Iraq. The levelised cost of electricity and capacity factor shows a considerable decrease and increase respectively, when the plant is backed up by a fossil fuel steam cycle under circumstances when a plant loses over 80% of the MW capacity due to drop in solar irradiance. To provide a comparision platform, for each city, a photovolitaic (PV) plant is designed with an indentical electric capacity to that of the CSP plant. Findings from this work confirm that CSP plants can provide a suitstanable and enviroemntl friendly solution to electrical power shortages in the country compared to the current PV trends.